Market and supermarket issues for development. Enhancing farmers' capacity to link with markets. - Campilan, D. (2012)
Research and development efforts to strengthen farmers’ linkage with markets often focus on the systematic assessment of market chains, formulation of pro-poor policy recommendations, and the introduction of macro level enabling mechanisms. Meanwhile there is growing recognition of the critical need for action-learning approaches for enhancing smallholder producers’ capacity to better manage farm businesses within dynamic market chains. Traditional agricultural extension generally deals with production-focused, technology-driven learning content. Yet it is now widely acknowledged that farmers also need to acquire knowledge, skills and attitude to improve their participation in and benefit from market chains. The main objective of this paper is to analyze key learning approaches in enhancing farmers’ capacity to link with markets, in particular by comparing: 1) crop management- and marketing-based curricular frameworks, 2) farmer-group and chain wide participatory processes, 3) classroom- and field-oriented learning settings, and 4) single-activity and season-long learning designs. The paper assesses the emerging trends in farmer capacity strengthening towards a more experiential learning process with a market chain perspective — as exemplified by the participatory market chain approach and farmer business school. It highlights experiences and lessons from the root and tuber crops sector, drawn from collaborative work by the International Potato Center and partners in developing countries of Asia, Latin America and Africa. Finally the paper identifies needs and opportunities to further improve capacity strengthening approaches, including their potential adaptation and upscaling across agricultural market chains and contexts.